2008
DOI: 10.1093/annonc/mdn169
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in gastric cancer: a new prognostic factor and a novel therapeutic target

Abstract: Gastric cancer is the second leading cause of cancer mortality in the world and its management, especially in advanced stages, has evolved relatively little. In particular, no targeted modality has so far been incorporated to its treatment armamentarium. HER2 overexpression is increasingly recognized as a frequent molecular abnormality, driven as in breast cancer by gene amplification. There is mounting evidence of the role of HER2 overexpression in patients with gastric cancer, and it has been solidly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
787
6
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,003 publications
(852 citation statements)
references
References 45 publications
46
787
6
13
Order By: Relevance
“…We have found that inhibition of nuclear import using wheat germ agglutinin abrogated the effect of EGFR inhibitors on DNA repair. 3 Therefore, we investigated the effects of blocking HER2 nuclear expression by using a construct lacking the putative NLS. In these experiments, the HER2-expressing cells showed no effect of trastuzumab treatment and indeed were less efficient at repairing ICL than the vectorexpressing controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that inhibition of nuclear import using wheat germ agglutinin abrogated the effect of EGFR inhibitors on DNA repair. 3 Therefore, we investigated the effects of blocking HER2 nuclear expression by using a construct lacking the putative NLS. In these experiments, the HER2-expressing cells showed no effect of trastuzumab treatment and indeed were less efficient at repairing ICL than the vectorexpressing controls.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased expression of HER2 has also been found in other malignancies including gastric and prostate cancers (3). Activation of HER2, primarily through heterodimerization with other members of the epidermal growth factor receptor (EGFR) family, results in downstream signaling through the Ras and phosphoinositide-3-kinase pathways (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] ErbB2 amplification or overexpression also seems to be associated with poorer prognosis, more aggressive disease and shorter survival in gastric cancer. [5][6][7] Preclinical and clinical studies of upper gastrointestinal adenocarcinomas, 2 and in particular, the large ToGA trial, which included adenocarcinomas of the stomach and gastro-oesophageal junction, have demonstrated that trastuzumab exerts antitumour activity on ErbB2-overexpressing tumours. 8 Most recently, this has led to the approval of the addition of trastuzumab to fluoropyrimidine/platinum-based therapies for patients with ErbB2-positive advanced gastric cancer by the European Medicines Agency (EMEA), the FDA and Health Canada.…”
mentioning
confidence: 99%
“…One potential therapeutic target is the HER family (19,20). HER2 overexpression or amplification has been reported in 6%-33% of gastric cancer and gastroesophageal junction, a similar rate to that observed in breast cancer (21)(22)(23)(24)(25). The largest analysis to date of the incidence of HER2 amplification in gastric cancer was from the Phase III ToGa trial, which evaluated the combination of trastuzumab with chemotherapy in patients with metastatic gastric cancer.…”
Section: Introductionmentioning
confidence: 98%